Comparative study of urinary sodium excretion in hypertensives versus normotensives - Ibrahim Mohsin; Zain Fatiwala; Habeeb M. Ahmed (Al Ameen Medical College, 2019)
Objective: To examine the pattern of urinary sodium excretion in hypertensive patients and comparison of the results with those from the normotensive subjects; as well this study further quantified the diurnal variations. Background: In healthy individuals, there is a diurnal variation in pattern of urinary sodium excretion, maximum sometime around midday and a minimum toward the end of sleep. Hence, this study is conducted to compare the pattern of urinary sodium excretion between hypertensive patients and normotensive subjects. Material and Method: The study was a hospital based cross-sectional, observational study. The study group consisted of two subsets, the hypertensive individuals (according to JNC 72 criteria), both for indoor and outdoor consultations and the normotensive group consisted of volunteers selected randomly. Study participants provided 8- hour urine collections carefully timed into three periods 6am-2pm, 2pm-10pm and 10pm-6am. Results: The mean excretion of sodium was double during morning hours in the normotensive patients (6 a.m. to 2 p.m.) 95.4 vs 45.1 to hypertensive patients and the reversal of this pattern in hypertensive patients where nocturnal excretion (10 p.m. to 6 a.m.) of sodium was almost double 97.6 as compared to their normotensive counterparts 56.9 (p value <0.001). Conclusion: Hypertensives have significant under excretion of urinary sodium in the day time and highest excretion during night time, which is a reversal pattern of urinary sodium excretion process in comparison to normotensives.